2007
DOI: 10.1016/j.mce.2006.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Is human chorionic gonadotropin directly involved in the regulation of human implantation?

Abstract: Please cite this article as: Licht, P., Fluhr, H., Neuwinger, J., Wallwiener, D., Wildt, L., Is human chorionic gonadotropin directly involved in the regulation of human implantation? Molecular and Cellular Endocrinology (2007), doi:10.1016/j.mce.2006 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 46 publications
2
115
0
5
Order By: Relevance
“…hCG was shown having direct paracrine effects on the endometrium that precede its endocrine role of rescuing the corpus luteum, and regulates IGFBP-1 and prolactin in decidualized human endometrial stromal cells [51][52][53][54]. Here, hCG did not affect MFGE8 gene expression levels, consistent with previous results from our laboratory showing no change in primary human endometrial epithelial cells [31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…hCG was shown having direct paracrine effects on the endometrium that precede its endocrine role of rescuing the corpus luteum, and regulates IGFBP-1 and prolactin in decidualized human endometrial stromal cells [51][52][53][54]. Here, hCG did not affect MFGE8 gene expression levels, consistent with previous results from our laboratory showing no change in primary human endometrial epithelial cells [31].…”
Section: Discussionsupporting
confidence: 91%
“…(protein score and mass-kD): annexin (182, 38690), actin (708, 41710-41766), glyceraldehide 3-phosphate dehydrogenase (47,36030), heat shock cognate (88, 70854), proteasome subunit alpha (52,29537), and tubulin alpha (110, 49863-50120). AFM imaging confirmed the presence of secreted membranous structures, likely microvesicles from the pellets after ultracentrifugation of the Ishikawa cells media.…”
Section: Il-6mentioning
confidence: 99%
“…According to our previous observations and those of other groups, hCG plays important paracrine roles in implantation, angiogenesis and immune tolerance (Perrier d'Hauterive et al 2004Edwards 2006;Licht et al 2007;Rao and Lei 2007). Because of Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Transcription of hCG begins before implantation (Jurisicova et al 1999), as shown in a study in which the hCG production in fluid that was removed from in vitro-cultured embryos was detected as soon as 170 h after insemination (Fishel et al 1984). In addition, the results of recent studies demonstrate that hCG plays a crucial role in regulating endometrial cell differentiation and the implantation process; it not only participates in these processes via its endocrine role, but also in a paracrine manner at the maternalfetal interface (Han et al 1999;Cameo et al 2004;Afshar et al 2007;Licht et al 2007). Blastocyst hCG increases endometrial secretion of proimplantatory leukaemia inhibitory factor (LIF; Perrier d' Hauterive et al 2004) and macrophage-colony stimulating factor (M-CSF; Licht et al 2001), increases stromal COX2 (cyclo-oxygenase 2) expression (Han et al 1996) and reduces the expression of the decidual marker IGF-BP1 (insulinlike growth factor binding protein 1) during the late secretory phase (Licht et al 2002;Fluhr et al 2006).…”
Section: Introductionmentioning
confidence: 92%
“…Low levels of hCG in the first trimester of pregnancy has long been considered as a predictor of miscarriage, ectopic pregnancy, and failure of IVF procedure [7][8][9]. Intensive studies have revealed that its function includes maintaining the production of steroid hormones and other growth factors in the corpus luteum, blastocyst implantation, uterine vascularization and angiogenesis, uterine quiescence, and immunological adaptation during pregnancy [16][17][18][19]. HCG, a glycoprotein hormone, is composed of identical alpha subunit similar to other glycoprotein hormones (LH, FSH, and TSH) in addition to a hormone-specific beta catalytic subunit [20].…”
Section: Discussionmentioning
confidence: 99%